Would you try it again? Dual effects of customer mindfulness on service recovery - Martinez, L. M.; Pacheco, N.; Ramos, F. R.; Bicho, M. (Journal of Retailing and Consumer Services, 2023)
Service failures have a negative impact on customer experience. Research in the field has looked for ways to reduce this negative impact, but little is known about the role of customer mindfulness in this context. Two quantitative scenario-based studies () were conducted. Study 1 (experimental, between-subject design) showed that mindfulness moderates the relationship between attributions of benevolence and post-purchase intention (i.e., stronger effects for low mindful customers). Study 2 (follow-up, within-subject design) showed that the level of customer mindfulness is positively associated with a preference for explanation as a service recovery tactic. This research highlights the dual effects (positive vs. negative) of customer mindfulness in the context of service failure.